Steroid pulse therapy in patients with encephalopathy associated with severe fever with thrombocytopenia syndrome. Issue 5 (May 2018) - Nakamura, Shingen; Azuma, Momoyo; Maruhashi, Tomoko; Sogabe, Kimiko; Sumitani, Ryohei; Uemura, Munenori; Iwasa, Masami; Fujii, Shiro; Miki, Hirokazu; Kagawa, Kumiko; Hiraga, Takashi; Kondo, Noriyasu; et al.
Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is a tick-borne infectious disease caused by the SFTS virus (SFTSV). Clinical symptoms of SFTS often involve encephalopathy and other central neurological symptoms, particularly in seriously ill patients; however, pathogenesis of encephalopathy by SFTSV is largely unknown. Herein, we present case reports of three patients with SFTS, complicated by encephalopathy, admitted to Tokushima University hospital: one patient was a 63-year-old man, while the other two were 83- and 86-year-old women. All of them developed disturbance of consciousness around the 7th day post onset of fever. After methylprednisolone pulse therapy of 500 mg/day, all of them recovered without any neurological sequelae. SFTSV genome was not detected in the cerebrospinal fluid of 2 out of the 3 patients that were available for examination. In these patients, disturbance of consciousness seemed to be an indirect effect of the cytokine storm triggered by SFTSV infection. We propose that short-term glucocorticoid therapy might be beneficial in the treatment of encephalopathy during early phase of SFTSV infection.